White Matter Abnormalities and Cognitive Deficit After Mild Traumatic Brain Injury: Comparing DTI, DKI, and NODDI - Huang, Sihong; Huang, Chuxin; Li, Mengjun; Zhang, Huiting; Liu, Jun (Frontiers in Neurology, 2022)
White matter (WM) disruption is an important determinant of cognitive impairment after mild traumatic brain injury (mTBI), but traditional diffusion tensor imaging (DTI) shows some limitations in assessing WM damage. Diffusion kurtosis imaging (DKI) and neurite orientation dispersion and density imaging (NODDI) show advantages over DTI in this respect. Therefore, we used these three diffusion models to investigate complex WM changes in the acute stage after mTBI . From 32 mTBI patients and 31 age-, sex- and education-matched healthy controls, we calculated six diffusion metrics based on DTI (fractional anisotropy and mean diffusivity), DKI (mean kurtosis) and NODDI (orientation dispersion index, volume fraction of intracellular water (Vic) and volume fraction of the isotropic diffusion compartment). We used tract-based spatial statistics to identify group differences at the voxel level, and we then assessed the correlation between diffusion metrics and cognitive function. We also performed subgroup comparisons based on loss of consciousness. Patients showed WM abnormalities and cognitive decline. And these two changes showed positive correlation. The correlation between Vic of the splenium of the corpus callosum and Digit Symbol Substitution Test scores showed the smallest p value (p=0.000, r=0.481). We concluded that WM changes, especially in the splenium of the corpus callosum, led to cognitive impairment in this study. Furthermore, the high voxel count of NODDI results and the consistency of mean kurtosis and the volume fraction of intracellular water in previous studies and our study showed the functional complementarity of DKI and NODDI to DTI.